Development of science subject-specific pedagogy to support disaster risk reduction in education: Its feasibility and influence - Haka, Nukhbatul Bidayati; Mauliana, Luckyta; Supriyadi, Supriyadi; Hamid, Abdul (IAIN Palangka Raya, 2023)
This development research aims to provide innovations to learning media in Biology learning. The model used in developing this media adopts the Borg & Gall development theory which is cut into 9 steps with a population of students in class XI MIPA. The instruments used are expert validation questionnaires, student response questionnaires, and critical thinking essay questions. The results of research in developing android-based virtual practicum media can improve critical thinking skills, become a simulation forum before carrying out activities in the laboratory (pre-lab), and become a solution to the shortage of laboratory facilities. The results of the validation of media experts get an average percentage of 91.66% with very decent criteria, material experts an average of 81.25% with very decent criteria, linguists produce 91.40% with very feasible criteria, and responses the percentage of students is 70.58% with proper criteria. The effectiveness of the media can be seen from the results of the hypothesis which gets Tcount